Faʿāliyah istiʿmāl biṭāqat al-kalimah ʿalā kafāʾat al-mufradāt :dirāsah kammiyyah li-ṭullāb al-faṣl al-sābiʿ fī al-madrasah al-mutawassiṭah al-ahliyyah al-Raḥmān, Ngelaban, Bandarkedungmulyo, Jombang - Nur Sholekhah; Lailatul Qomariyah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
This study examines how the use of word cards on the vocabulary efficiency of seventh grade students at Mts Ar Rohman Nglaban bandet jombang? How to teach vocabulary to seventh grade students at Mts Ar Rohman Nglaban bandet jombang? And how does the use of word cards affect the vocabulary efficiency of seventh grade students Mts Ar rohman Nglaban bandet jombang?. This research method is quantitative research data collection, tests, questionnaires and documentation. Then the samples were analyzed in pairs. The results of the study: 1) Vocabulary learning in the seventh semester still uses traditional methods, where the teacher mentions one of the vocabulary, then the student pronounces the vocabulary, then the teacher gives the meaning of the vocabulary, and this is done repeatedly until the student master it. This method is of less interest to students, because students are bored with a monotonous class atmosphere and have an impact on students' lack of enthusiasm to study in the classroom. 2) The use of word cards on the vocabulary efficiency of seventh grade students at Mts Ar rohman Nglaban bandet jombang. After practicing the use of word cards in the seventh chapter in vocabulary learning. Through questionnaires distributed to students tested for validity beforehand. The result was that forty-three percent of students who answered agreed with the use of word cards as a means to improve the ability to memorize the vocabulary of seventh grade students at Mts Ar rohman Nglaban bandet jombang. 3) The effect of the use of word cards on the vocabulary efficiency of seventh grade students in Mts Ar Rohman Nglaban bandet jombang. From the results of the double value sample test before and after using the word card obtained 0.926 sig which is more than 0.05, meaning that there is no effect of the use of the word card on the efficiency of vocabulary, which means a lack of mastery of Arabic and a lack of interest in using it.